Shortest Path Problem in Network with Quadripartitioned Neutrosophic Arc Length - Broumi Said; Yuhao Su; M. Parimala; Yekini Shehu (Winaya Inspirasi Nusantara Foundation, 2025)
Many extensions and generalizations of neutrosophic sets have been introduced and studied in the literature. Quadripartitioned single valued neutrosophic set becomes an important tool in solving various types of decision making problems, medical diagnosis problems, clustering,... etc. The neutrosophic graph has still been a powerful tool for modeling and designing indeterminate networks. Quadripartitioned single valued neutrosophic graph is a generalization of single valued neutrosophic graph. In this chaptre, we formulate the shortest path (SP) problem in Quadripartitioned single valued neutrosophic environment. Here, the costs related to arcs are taken in the form of Quadripartitioned single valued neutrosophic numbers (QSVNNs). A numerical example also included illustrating our proposed method for finding the neutrosophic shortest path.